Taxonomy of the leafhopper genus Adama (Hemiptera: Cicadellidae: Deltocephalinae: Selenocephalini: Adamina) with description of a new species from Botswana - Xu, Deliang; Zhang, Yalin (Zootaxa, 2023)
The leafhopper genus Adama is reviewed with the description of a new species, Adama (Zinjella) serriformis sp. nov., from Botswana. An updated checklist with distributions and a key to species of this subgenus are also provided. The type specimen of this new species is deposited in the Natural History Museum, London, U.K. (BMNH).